Labor relations in globalized food - Bonanno, Alessandro; Cavalcanti, Josefa Salete Barbosa (Bingley, U.K. : Emerald, 2014)
This book looks at labor in agriculture and food in a global era by studying salient characteristics of the conditions and use of labor in global agri-food. Written by experienced and also emerging scholars, the chapters present a wealth of empirical data and robust theorizations that allow readers to grasp the complexity of this topic.
Globalization and change in labor relations in fruit regions of Brazil and Argentina / Josefa Salete Barbosa Cavalcanti, Mónica Isabel Bendini -- Restructuring global labor markets : recruitment agencies and work relations in the wild berry commodity chain / Charlotta Hedberg -- Capitalization strategies and labor in agricultural machinery contractors in Argentina / José Muzlera -- Labor relations and issues in the poultry sector in Mexico / Gilberto Aboites, Francisco Martínez -- Petty commodity production in the neoliberal phase of global capitalism : the case of grape production in Çanakkale / Burcu Saka -- From workers' cooperative to hired-labor farm : accommodating to global market pressures in Slovak post-socialist agriculture / Jana Lindbloom -- Agriculture with or without farmers : a comparative analysis of adaptation and resistance among family farmers in Argentina and Colombia / Sandra Lucía Fonseca Santanilla, Carolina Carvajal Castro -- State and regulation of labor relations in the sugarcane fields of Brazil / Maria Aparecida de Moraes Silva, Marilda Aparecida Menezes, Jadir Damião Ribeiro -- Labor, gender and political conflicts in the global agri-food system : the case of the agri-export model in Murcia, Spain / Andrés Pedreño, Elena Gadea, Carlos de Castro -- Effects of the division of labor on the distribution of fresh produce : the case of Argentina / Alberto Arce, María Laura Viteri, Mónica Mateos -- The processing of palm oil in Chiapas, Mexico : resistance and alternatives / Héctor B. Fletes-Ocón, Alessandro Bonanno -- Conclusions : labor between exploitation and resistance / Josefa Salete Barbosa Cavalcanti, Alessandro Bonanno.
Includes index.
Print version record
Keywords: Social Science -- Agriculture & Food; Social Science -- Sociology -- Rural; Sociology: work & labour; Food & society; Food industry and trade